The Millennium Villages Project and Local Land Values: Using Hedonic Pricing Methods to Evaluate Development Projects. (January 2018) - Michelson, Hope; Tully, Katherine
Highlights: We use hedonic analysis of land values to assess an anti-poverty development project. We use data on land transactions to study the effects of The Millennium Villages Project (MVP). We find no effect on local land values despite considerable project investment in public goods. Summary: This paper uses hedonic analysis to estimate the impact of an area-based anti-poverty project on land values in a developing country. Economic theory would suggest that benefits of area-based programs would be capitalized into land prices, as supply is relatively fixed compared to other factors of production. While revealed preference methods have been applied widely in the field of environmental economics, they have not yet been used to evaluate an international development project. We study the effects of The Millennium Villages Project (MVP) in Sauri, Kenya. Using administrative data from the Kenyan government on prices for land bought and sold within the MVP (established in 2005) and for land bought and sold in the surrounding area during 1999–2013, we estimate the project's effect on local land prices. We find no evidence that the MVP investments led to an increase in land prices within project areas. This research represents the first work to use hedonic analysis of land values to assess an international development project.